Ordonans o handlu lądowym z 1673 roku (Kodeks Savary’ego) - Klimaszewska, Anna (Czasopismo Prawno-Historyczne, 2009)
The Ordinance of Commerce was the first codification of commercial law which contained many provisions that regulated the accepted commercial practices. Consequently, it became very successful both in France and beyond its borders. It also created the French doctrine of commercial law. However, objective factors as well as a narrow approach of the main legislator – creator of the Act – led to a situation in which the ordinance, although useful for the practitioners, or traders, presented many imperfections on the theoretical side. Members of the Committee were too prudent and avoided general, or abstract concepts, in consequence of which the Code Savary was incapable of fully protecting "traders acting in good faith against ignobility." Moreover, since the Act allowed a longer litigation process and thus created higher costs, at the same time diminishing the efficiency of the Court work. Last but not least, the Ordinance of Commerce met with little social understanding and many difficulties in its application.